Disproving claims for small-bodied humans in the Palauan archipelago. (6th December 2017) - Stone, Jessica H.; Fitzpatrick, Scott M.; Napolitano, Matthew F.
Abstract: Abstract : Recent excavation at Ucheliungs Cave in Palau has provided new evidence in the debate concerning the colonisation of the Palauan archipelago. An abundance of faunal material and the presence of transported artefacts contradict a previous interpretation that the site represents an early burial cave containing purported small-bodied humans. New radiocarbon dates suggest long-term use of the cave for both mortuary activity and small-scale marine foraging that may slightly precede the accepted date for the earliest human occupation of Palau. The results of this research here discount earlier claims for insular dwarfism among the earliest inhabitants of these islands.